2018
DOI: 10.1002/cctc.201701933
|View full text |Cite
|
Sign up to set email alerts
|

Covalent or Non‐Covalent? A Mechanistic Insight into the Enantioselective Brønsted Acid Catalyzed Dearomatization of Indoles with Allenamides

Abstract: The reaction mechanism of the enantioselective Brønsted acid catalyzed dearomatization of C(2),C(3)‐disubstituted indoles with allenamides is investigated by means of density functional theory (DFT) calculations and ESI‐MS analysis. The first step of the process (rate‐determining step) is the formation of a covalent adduct between allenamide and the chiral organo‐promoter. The resulting chiral α‐amino allylic phosphate undergoes dearomative condensation with indoles. In the first step, the indole moiety remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…Subsequently, the reaction mechanism was investigated by means of density functional theory calculations and electrospray ionization mass spectrometry analysis. 7 The rst step of the process (rate determining step) was the formation of a covalent adduct between the allenamide and chiral organopromoter. The resulting chiral a-amino allylic phosphate undergoes dearomative condensation with indoles.…”
Section: Chiral Phosphoric-acid-catalyzed Functionalization Of Allenamentioning
confidence: 99%
“…Subsequently, the reaction mechanism was investigated by means of density functional theory calculations and electrospray ionization mass spectrometry analysis. 7 The rst step of the process (rate determining step) was the formation of a covalent adduct between the allenamide and chiral organopromoter. The resulting chiral a-amino allylic phosphate undergoes dearomative condensation with indoles.…”
Section: Chiral Phosphoric-acid-catalyzed Functionalization Of Allenamentioning
confidence: 99%
“…The group performed in-depth mechanistic investigations, including NMR studies to assess the role of the counterion in the gold-catalyzed reaction [23] and theoretical calculations and ESI-MS analysis for the Brønsted acid catalyzed one. [24] Interestingly, the Pd(0)-catalyzed reaction of similar tetrahydrocyclopenta[b]indoles 38a in the presence of 2,3-allenyl carbonates 39 and trapping agents (acyl chlorides), gave enamine derivatives 42 in which the allene was still present in the final structure (Scheme 9a). [25] The reaction was carried out in the presence of a base, being BSA (N,O-bis(trimethylsilyl)acetamide) the one that gave the best results, and 1 equivalent of Et 3 B to activate the indole through N-B bond formation.…”
Section: Eurjocmentioning
confidence: 99%
“…The group performed in‐depth mechanistic investigations, including NMR studies to assess the role of the counterion in the gold‐catalyzed reaction [ 23 ] and theoretical calculations and ESI‐MS analysis for the Brønsted acid catalyzed one. [ 24 ]…”
Section: Intermolecular Reactionsmentioning
confidence: 99%
“…Lowering the temperature to 0°C further increased the enantioselectivity to 85% ee (entry 11). However, change of N-protecting groups as in 6 and 8 (entries [13][14], as well as employment of different allenamides 2 b-e [11] in place of 2 a were largely unsuccessful, affording lower yields and/or enantioselectivities. The product 9 COMMUNICATIONS DOI: 10.1002/adsc.202000083…”
mentioning
confidence: 99%
“…In fact, Bandini and coworkers revealed that such possibility was more favourable than path (a), according to DFT computational study. [13] Finally, the indolo [2,3-b]quinoline 5 a could be functionalized into alcohols 10 and 11 as in Scheme 3. Protection of aminal nitrogen, followed by hydrolysis afforded unstable aldehyde, which was reduced in-situ into 10 in excellent overall yields (84%) with no racemization.…”
mentioning
confidence: 99%